2014
DOI: 10.1155/2014/698178
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Activities of Actinobacteria Isolated from Tropical Mangrove Sediments in Malaysia

Abstract: The aim of this study was to isolate and identify Actinobacteria from Malaysia mangrove forest and screen them for production of antimicrobial secondary metabolites. Eighty-seven isolates were isolated from soil samples collected at 4 different sites. This is the first report to describe the isolation of Streptomyces, Mycobacterium, Leifsonia, Microbacterium, Sinomonas, Nocardia, Terrabacter, Streptacidiphilus, Micromonospora, Gordonia, and Nocardioides from mangrove in east coast of Malaysia. Of 87 isolates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 65 publications
7
143
1
2
Order By: Relevance
“…The members of Streptomyces are well-known for their ability to produce a variety of bioactive compounds with different bioactivities such as antibacterial (Schumacher et al, 2003; Ramesh and Mathivanan, 2009; de Lima Procópio et al, 2012; Kumar et al, 2014; Lee et al, 2014a,b; Ser et al, 2016a), antifungal (Lam, 2006), antiviral (Ara et al, 2014), immunosuppressive (Kino et al, 1987), anticancer, and antioxidant properties (Ser et al, 2015a; Tan et al, 2015, 2016). These bioactive compounds have important applications in various fields.…”
Section: Streptomyces Spp As Biocontrol Agents Against M Oryzaementioning
confidence: 99%
See 1 more Smart Citation
“…The members of Streptomyces are well-known for their ability to produce a variety of bioactive compounds with different bioactivities such as antibacterial (Schumacher et al, 2003; Ramesh and Mathivanan, 2009; de Lima Procópio et al, 2012; Kumar et al, 2014; Lee et al, 2014a,b; Ser et al, 2016a), antifungal (Lam, 2006), antiviral (Ara et al, 2014), immunosuppressive (Kino et al, 1987), anticancer, and antioxidant properties (Ser et al, 2015a; Tan et al, 2015, 2016). These bioactive compounds have important applications in various fields.…”
Section: Streptomyces Spp As Biocontrol Agents Against M Oryzaementioning
confidence: 99%
“…These bioactive compounds have important applications in various fields. For example, approximately 75% of commercially useful antibiotics were derived from the genus Streptomyces and they are thus the primary antibiotic-producing organisms exploited by the pharmaceutical industry (Pelaez, 2006; Lee et al, 2014b; Kashif et al, 2016). Streptomyces strains also have important applications in the agricultural field through their biological control potential against phytopathogens, particularly phytopathogenic fungi (Gonzalez-Franco and Robles-Hernandez, 2009).…”
Section: Streptomyces Spp As Biocontrol Agents Against M Oryzaementioning
confidence: 99%
“…Mangrove is one of the world's most dynamic environments which occupies millions of hectors across the world coastal areas and it has been a habitat to various flora and fauna of terrestrial, freshwater, and marine species (Mangamuri et al, 2012; Lee et al, 2014e). According to the report by Giri et al (2011), the largest extent of mangroves is found in Asia; and Malaysia is one of the most mangrove-rich countries in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Actinobacteria, especially the genus Streptomyces , are major producers of bioactive metabolites [1] and account for nearly 75% of the total antibiotic production available commercially [2, 3]. A few decades ago, antibiotics were considered as wonder drugs since they warded off deadly pathogens leading to eradication of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%